Wanita dan Toleransi Beragama (Analisis Psikologis) - Maimanah, Maimanah (IAIN Antasari Banjarmasin, 2013)
It has become the responsible of all parties to promote public toleratnce in the mids of religious pluralism in Indonesia. The issue of tolerance is a matter of religious awareness which concerns with the psychological aspect, so that it is significant to present the issue of tolerance with psychological approach. Women as one of the active religious followers have psychological potential to exhibit tolerance. Various roles that women run have coloured themselves with the essence of humanity that all human whatever ethnicity and religion they proclaim are one big family who should live in harmony.